2010
DOI: 10.1158/0008-5472.can-09-2505
|View full text |Cite
|
Sign up to set email alerts
|

CD44 Attenuates Activation of the Hippo Signaling Pathway and Is a Prime Therapeutic Target for Glioblastoma

Abstract: Glioblastoma multiforme (GBM) is the most aggressive brain tumor that, by virtue of its resistance to chemotherapy and radiotherapy, is currently incurable. Identification of molecules whose targeting may eliminate GBM cells and/or sensitize glioblastoma cells to cytotoxic drugs is therefore urgently needed. CD44 is a major cell surface hyaluronan receptor and cancer stem cell marker that has been implicated in the progression of a variety of cancer types. However, the major downstream signaling pathways that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
165
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(176 citation statements)
references
References 49 publications
9
165
2
Order By: Relevance
“…, and Oct4 þ ) similar or parallel to those already described for other solid tumors (11)(12)(13)(35)(36)(37)(38)(39)(40)(41)(42)(43). Second, analysis of gene microarray data from the cells in the macrobeads indicate that pathways which have been associated with stem cells, such as the Wnt pathway, are enhanced compared with the same gene pathways in the total population of RENCA cells in monolayer culture.…”
Section: Discussionsupporting
confidence: 76%
“…, and Oct4 þ ) similar or parallel to those already described for other solid tumors (11)(12)(13)(35)(36)(37)(38)(39)(40)(41)(42)(43). Second, analysis of gene microarray data from the cells in the macrobeads indicate that pathways which have been associated with stem cells, such as the Wnt pathway, are enhanced compared with the same gene pathways in the total population of RENCA cells in monolayer culture.…”
Section: Discussionsupporting
confidence: 76%
“…Signaling through CD44 has been previously investigated, and downstream ERK and PI3K-Akt pathway activation or Hippo cascade inhibition were described (36)(37)(38)(39)(40). Moesin overexpression in glioblastoma and NHA cells activated the PI3K-Akt, ERK, and p38 MAPK pathways (Fig.…”
Section: Moesin Is Constitutively Phosphorylated In Glioblastoma Cellsmentioning
confidence: 99%
“…CD44 serves as a surface receptor for ECM molecules such as HA and CSPGs (Ranuncolo et al 2002). CD44 receptor is overexpressed in glioma cells in vitro (Wiranowska et al 2000, Yu et al 2010) and found in vivo at the leading edge of glioma at the brain-tumor interface (Wiranowska et al 2006). The HA-CD44 interaction and CD44 shedding from the cell surface were found to be associated with glioma cell motility, migration, and infiltration into the normal brain parenchyma (Annabi et al 2005).…”
Section: Extracellular Matrix Molecules In Glioma 341 Glycosaminoglmentioning
confidence: 99%